Kajian Penggunaan Aplikasi Android Sebagai Platform Untuk Menghitung Indeks Massa Tubuh (IMT) - Lathifah Hanum; Dwiny Meidelfi; Aldo Erianda (Indonesian Society of Applied Science, 2020)
Body Mass Index or BMI is an indicator used to measure body weight whether classified as ideal or not. A person's BMI determines by comparing body weight and height which then predicts the standard body value category from the results of renewal. BMI is often used as a measurement tool for the body in carrying out daily diet programs. However, BMI is also often used as a reference for health risks, as a determinant of coronary heart disease or as a measurement tool for diets for people with diabetes mellitus. Using a smartphone that continues to increase over time can be used for ease in calculating a person's BMI. With various methods of making existing systems, such as manual, Bluetooth Low Energy (BLE) or image processing. The manual method requires weight and height data input which is not necessarily the same every time. While BLE requires an external device other than a smartphone to calculate weight and height. From the studies conducted, the image processing method is the most effective. The image processing method takes the data needed to calculate the BMI through the inputted image without the need to manually input data or use an external device other than a smartphone.